Parental Interference in Offspring's Mate Choice: Sets of Actions and Counteractions Based on Both Perspectives - Fišerová, Anna; Havlíček, Jan; Urban, Marek; Urban, Kamila; Štěrbová, Zuzana (Archives of sexual behavior, 2023)
Mate choice in humans is specific by the involvement of kin both in partner choice and in the functioning of the relationship. The influence of relatives ranges from providing advice all the way to arranged marriages. Existing research so far tended to map neither the actual parental interventions and further reactions (counteractions) nor the independently pursued behavior (actions) by which the offspring or their partners assert their interests. This study identified such sets of behaviors through semi-structured individual interviews with members of 20 dyads of adult offspring and their biological parents (five son-mother, five son-father, five daughter-mother, and five daughter-father dyads). Thematic analysis revealed sets of parental actions aimed at the offspring, their partners, and the couple as a whole, as well as further counteractions (reactions to parental interference) and independently pursued behavior (actions) of the offspring and their partners aimed at the parents in the context of the offspring's previous or current relationship. Our findings showed that parental interference differed depending on the recipient: toward the couple were applied mainly indirect and supportive parental actions, whereas when facing their offspring or offspring's partner, parents' actions were more direct and disruptive. Our results thus indicate the importance of reporting about actual interactions which differ from the hypothetical settings used in prior studies by lower intensity. Moreover, by interviewing both members of dyads, we expanded the sets of actions and counteractions identified by prior studies and managed to limit self-reporting bias.
Keywords: Mate choice; Parents; Manipulation; ženské pohlaví; dospělí; Humans; Adult; Female; matky; Mothers; Parental influence; Manipulation tactics; rodiče; lidé